Viral Diseases of Strawberry: PP273, rev. 11/2021 - Moyer, Catalina; Whitaker, Vance; Peres, Natalia A. (EDIS, 2021)
Viral diseases in strawberry are not easily detected because most single virus infections are symptomless on commercial cultivars. However, virus outbreaks have the potential for epidemics and economic losses. A mixed virus infection of Strawberry Mild Yellow Edge Virus (SMYEV) and Strawberry Mottle Virus (SMoV) was identified in several southeastern states during the 2012-13 season, resulting in millions of dollars in losses. This updated version of a previous publication offers basic information on viral diseases of strawberry, with emphasis on viruses of potential threat to the strawberry industry in Florida. The primary target audience of this publication includes growers and industry personnel, extension agents and pathologists working with strawberry. Originally published April 2010: Moyer, Catalina, Vance Whitaker, and Natalia Peres. 2010. “Viral Diseases of Strawberries”. EDIS 2010 (4). https://journals.flvc.org/edis/article/view/118602.